Sistem Monitoring Suhu Dan Jumlah Pengunjung Kafe Berbasis Cloud Computing - Fachru Ramadhan; Hanriyawan Adnan Mooduto; Fitri Nova (SOTVI - Society of Visual Informatics, 2021)
Currently, Indonesia is being faced with the COVID-19 pandemic, to prevent being infected with the corona virus, it is to implement health protocols, especially in public places such as shopping centers to airports. The method taken by the Indonesian government in reducing the spread of the corona virus is by implementing PPKM (Enforcement of Community Activity Restrictions) which is one of the requirements for restaurants/cafes, namely limiting the number of visitors to eat in places that are allowed to be around 25% and checking the temperature of restaurant/cafe visitors. The Cloud Computing implementation tool on the temperature monitoring sistem and the number of visitors can assist in the implementation of health protocols in checking the body temperature of visitors at your cafe and make it easier for cafe owners to monitor the number of visitors so that when workers allow an increase in the number of visitors, it can be immediately known through a linked website. with tools.